A PROSPECTIVE COMPARATIVE STUDY TO ASSESS THE IMPACT OF MATERNAL BODY MASS INDEX ON OBSTETRIC OUTCOME - Verma, Gajendra Singh; Meena, Uma Kumari; Mathur, Sadhna; Yadav, Komal (International Journal of Medical and Biomedical Studies, 2021)
Background: The increasing prevalence of obesity in young women is a major public health concern. These trends have a major impact on pregnancy outcomes in these women. Methods: Hospital based prospective comparative study was conducted on 50 women in each group including normal, high and low maternal BMI. Result: Preeclampsia complicated 16% of overweight pregnancies while it was 2.00% in underweight group and 10.00% in normal weight group. The difference was statistically highly significant (p = 0.01). Conclusion: Maternal BMI shows strong associations with pregnancy complications. Attempt should be made to prevent obesity in women of childbearing age and encourage weight loss to attain ideal weight before pregnancy. Keywords: BMI, Obese, Maternal out come.